2023
DOI: 10.3390/life13030828
|View full text |Cite
|
Sign up to set email alerts
|

Melanoma Brain Metastases: A Systematic Review of Opportunities for Earlier Detection, Diagnosis, and Treatment

Abstract: Introduction: Melanoma continues to represent the most serious skin cancer worldwide. However, few attempts have been made to connect the body of research on advanced melanoma. In the present review, we report on strides made in the diagnosis and treatment of intracranial metastatic melanoma. Methods: Relevant Cochrane reviews and randomized-controlled trials published by November 2022 were systematically retrieved from the Cochrane Library, EMBASE, and PubMed databases (N = 27). Search and screening methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“… 21 Although significant advances have been made in current treatments and with the implementation of dual therapies, chemotherapy, immunotherapy, or combinations, survival has been described from 5 to 9 months, very similar to our reported data. 22 According to Thompson et al, their systematic review found a difference of 6 months in survival in patients treated only with surgery versus those treated with radiotherapy alone (10 months versus four months, respectively). 23 Like our findings, the median survival in patients treated with radiotherapy alone was five months, and for patients treated with surgery, it was 13 months for metastatic lesions to the CNS.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Although significant advances have been made in current treatments and with the implementation of dual therapies, chemotherapy, immunotherapy, or combinations, survival has been described from 5 to 9 months, very similar to our reported data. 22 According to Thompson et al, their systematic review found a difference of 6 months in survival in patients treated only with surgery versus those treated with radiotherapy alone (10 months versus four months, respectively). 23 Like our findings, the median survival in patients treated with radiotherapy alone was five months, and for patients treated with surgery, it was 13 months for metastatic lesions to the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, conducted by Gaudy-Marqueste C. et al, the median overall survival in BRAF wild-type patients treated with immunotherapy after SRS was 12.3 months [38]. Diaz, M.J. et al, in a systematic review carried out in 2023, reveal that the current treatment of brain metastases in malignant melanomas is directed towards the combination of stereotactic radiosurgery (SRS) and immunotherapeutic agents [39].…”
Section: Stereotactic Radiosurgery With Immunotherapymentioning
confidence: 99%
“…Some of the specific pathways or receptors with mutations leading to solid tumors include epidermal growth factor receptor EGFR , ALK , KRAS , ROS1 , BRAF , and HER2 , which can be treated by drugs targeting those specific mutations. Many of the targeted drugs are small molecules which can cross the blood–brain barrier and thus are relatively effective in the upfront treatment of BM harboring these mutations [ 5 , 6 , 7 ]. However, in the absence of genetic targetable drivers, RT is typically used, sometimes in conjunction with surgery as the primary treatment.…”
Section: Introductionmentioning
confidence: 99%